Upper gastrointestinal symptoms and associated endoscopic and histological features in patients receiving immune checkpoint inhibitors. (4th May 2019) - Tang, Tenglong; Abu-Sbeih, Hamzah; Luo, Wenyi; Lum, Phillip; Qiao, Wei; Bresalier, Robert S.; Richards, David M.; Wang, Yinghong
Abstract: Background: Immune checkpoint inhibitors (ICIs) have demonstrated effectiveness in treating many malignancies. Gastrointestinal (GI) adverse events are commonly reported; however, few reports describe upper GI tract toxic effects. We aimed to describe clinical features of upper GI injury related to ICI. Methods: We studied consecutive patients who received ICIs between April 2011 and March 2018 and developed upper GI symptoms requiring esophagogastroduodenoscopy (EGD). Results: Sixty patients developed upper GI symptoms between ICI initiation and 6 months after the last infusion. Among patients who had both EGD and colonoscopy ( n  = 38), 21 had endoscopic evidence of inflammation involving both the upper and lower GI tract. Overall, histological signs of inflammation of the stomach were evident in 83% of patients, but inflammation of the duodenum in 38%. Total of 42 patients had other risk factors of gastritis, i.e., chemotherapy, radiotherapy, and non-steroidal anti-inflammatory drugs. Only isolated gastric inflammation was seen on endoscopy in patients without these risk factors. The rates of ulceration were similar in the cohorts with and without other risk factors for gastritis. Isolated upper GI inflammation was related to anti-PD-1/L1 in 47% of patients. Immunosuppressive therapy in our cohort with upper GI toxicity consisted of steroids (42%) and infliximab or vedolizumab (23%). Most isolated upper GI symptoms were treated with proton pump inhibitors (65%) or H2 blockers (35%). Conclusion: We observed a correlation between ICI use and onset of upper GI inflammation even when other risk factors were excluded. Gastric involvement was evident more often than duodenal involvement on endoscopic and histological level.